Micellar Effect on the Reaction of Acid Green-16 with K2S2O8 Ion: Influence of Salts and Organic Solvents - M. Joshi, Hitendra; Nagar, T.N. (Asian Journal of Chemistry, 2010)
Cationic micelles of cetyl trimethyl ammonium bromide (C16TABr) increase the rate of reaction of triphenylmethyl carbonium ions with S2O82– ion whereas the anionic micelles of sodium dodecyl sulphate (SDS) inhibit this rate. The addition of monohydric alcohols, viz., n-butanol, ethanol and solvents like acetone and dimethylformamide decreases the cationic micellar catalysed rate, while on the other hand increases the anionic micellar inhibited rate. The influence of electrolytes in the presence of C16TABr has also been analysed.